2018
DOI: 10.3389/fcell.2018.00049
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Insulin-Producing Cells From Human Embryonic Stem Cells Underhypoxic Condition for Cell Based Therapy

Abstract: Diabetes mellitus (DM) is a group of diseases characterized by abnormally high levels of glucose in the blood stream. In developing a potential therapy for diabetic patients, pancreatic cells transplantation has drawn great attention. However, the hinder of cell transplantation for diabetes treatment is insufficient sources of insulin-producing cells. Therefore, new cell based therapy need to be developed. In this regard, human embryonic stem cells (hESCs) may serve as good candidates for this based on their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…Furthermore, chronic elevated serum levels of free fatty acids, seen in obesity and T2DM, induce lipotoxicity in beta-cells and suppress their insulin secretion ability (85). To alleviate chronic inflammation, overcome insulin resistance (IR) and to prevent β-cell apoptosis, stem cells or stem cell derivatives such as insulin-producing cells (IPCs) and exosomes have been suggested (86)(87)(88)(89). Their effects are believed to be mainly due to their anti-inflammatory activities.…”
Section: Pancreasmentioning
confidence: 99%
“…Furthermore, chronic elevated serum levels of free fatty acids, seen in obesity and T2DM, induce lipotoxicity in beta-cells and suppress their insulin secretion ability (85). To alleviate chronic inflammation, overcome insulin resistance (IR) and to prevent β-cell apoptosis, stem cells or stem cell derivatives such as insulin-producing cells (IPCs) and exosomes have been suggested (86)(87)(88)(89). Their effects are believed to be mainly due to their anti-inflammatory activities.…”
Section: Pancreasmentioning
confidence: 99%
“…Such ability to pre-determine cell fate and produce multiple cell lineages holds vast possibilities in the field of regenerative medicine. This has sparked a revolution in the management of several diseases, such as Parkinson's disease and diabetes [79][80][81]. In the cornea, a few studies have reported the differentiation of ESCs to express CEC-like phenotypes.…”
Section: Other Experimental Sources Of Corneal Endothelial Progenitorsmentioning
confidence: 99%
“…It is expected that this therapeutic method should produce, store, and supply insulin to maintain glucose homeostasis. Cell-based therapies are aimed at producing functional insulin-secreting β-cells to completely cure diabetes (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%